Silicon-carbon negative electrode material and preparation method thereof

By depositing a metal oxide layer on the surface of silicon-carbon composite particles and annealing, the problems of structural breakage and interface side reaction of silicon-carbon anode materials during circulation are solved, and the performance of high capacity and high efficiency lithium-ion battery is achieved.

CN119133393APending Publication Date: 2024-12-13YINSI (NINGBO) TECH CO LTD

Patent Information

Application Number
CN202411244090.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing silicon-carbon anode materials have structural fragmentation due to volume expansion and contraction during circulation, resulting in thickening of the interface layer of the solid electrolyte, consuming electrolyte and lithium ions, and reducing Coulomb efficiency and stability.

Method used

A metal oxide layer is deposited on the surface of silicon-carbon composite particles by atomic layer deposition method, and the silicon-carbon negative electrode material is prepared by annealing treatment, which inhibits the interface side reaction between the electrolyte and the substrate surface, and improves the structural stability and conductivity of the material.

Benefits of technology

The high capacity (1800-2300mAh/g) and high first charging efficiency (90-95%) of silicon carbon anode material were achieved, and the capacity retention rate reached 88.5% after 100 weeks of cycle, significantly improving the electrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133393A_ABST
    Figure CN119133393A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode material and a preparation method thereof, and belongs to the technical field of lithium ion battery negative electrode materials. The preparation method comprises the following steps: depositing a metal oxide layer on the surface of a silicon-carbon composite particle by adopting an atomic layer deposition method, and annealing the silicon-carbon composite particle coated with the metal oxide layer to obtain the silicon-carbon negative electrode material. According to the method disclosed by the invention, the negative electrode material has the structural stability of a porous material and has good conductivity and corrosion resistance, so that the material inhibits the dissolution of carbon and silicon elements at an interface, the increase of the thickness of an SEI film organic substance at the interface in the recycling process of the material is inhibited, and the transmission of lithium ions is more facilitated; and the rate capability of the Si / C composite material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a silicon-carbon negative electrode material and a preparation method thereof. Background Art

[0002] With the growth of portable electronic products and electric vehicle markets, the demand for high energy density lithium-ion batteries is increasing. At present, the theoretical specific capacity of silicon anode (4200mAh g -1 ) is about the commercial graphite anode (372mAh g -1 ) and has a suitable operating voltage (0.4V), making it a very promising negative electrode material.

[0003] However, Si is affected by lithium ions (Li + ) will produce a huge volume expansion (>300%). + The volume shrinks and changes repeatedly with the increase of the number of cycles. This volume change will not only cause the continuous cracking and fragmentation of Si, but also cause the disintegration, fracture and electrical isolation of Si and the electrode. Continuous fragmentation will also cause the continuous destruction and thickening of the solid electrolyte interface (SEI), rapidly consuming the electrolyte and Li + , resulting in low Coulombic efficiency (CE) of silicon negative electrode, rapid capacity decay, and sharp decline in stability. In addition, the low intrinsic electronic conductivity of Si is also one of the factors that seriously restrict the commercial application of silicon negative electrode.

[0004] The most effective way to overcome the challenges of practical application of Si-based negative electrodes is to rationally design nano-Si and effectively combine it with carbon materials. The expansion of Si negative electrodes is alleviated by nano-sizing, and silicon is made into nanospheres, nanowires, etc.; Patent CN 118367119A forms a surface coating on the surface of the carbon material core through an organic modifier, which improves the rate performance of the material, but the organic modifier is prone to decomposition, resulting in an increase in the SEI film on the surface of the core, which is not conducive to the transmission of lithium ions. Patent CN 115966684A uses porous carbon as a matrix and obtains a silicon-carbon composite material with a Si nanometer size of <10nm by silane deposition. The porous carbon matrix used in this method does not mention the problem of excessive specific surface area causing the SEI film to increase during the cycle, thereby exacerbating the consumption of the electrolyte; Patent CN 117457873 A uses porous carbon as a matrix and obtains a three-dimensional porous carbon skeleton structure by vacuum evaporation. The porous silicon-carbon matrix obtained by this method does not mention whether it will have an interfacial side reaction with the electrolyte, resulting in the accumulation and thickening of the material SEI film, which is not conducive to the transmission of lithium ions.

[0005] Therefore, how to obtain a high-performance silicon-carbon negative electrode material and its preparation method is a technical problem that needs to be solved at present. Summary of the invention

[0006] The purpose of the present invention is to provide a silicon-carbon negative electrode material and a preparation method thereof, so as to solve the technical problems of the stability of the pore structure of the existing porous matrix and the side reaction between the matrix surface and the electrolyte.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0009] (1) obtaining a metal oxide layer on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the metal oxide layer;

[0010] (2) annealing the silicon-carbon composite particles coated with the metal oxide layer to obtain a silicon-carbon negative electrode material;

[0011] The metal oxide contained in the metal oxide layer is M x O y , wherein M is Ta, Al, Ti or Zr, 0<x≤2, 0<y≤5.

[0012] Furthermore, the atomic layer deposition method comprises the following steps:

[0013] a. Loading silicon-carbon composite particles on a reaction chamber carrier, evacuating the reaction chamber, and passing an inert gas;

[0014] b. Using an inert gas as a carrier gas, a reaction precursor is added into the reaction chamber in a pulsed manner for deposition;

[0015] c. After the deposition is completed, the reaction chamber is evacuated by passing inert gas;

[0016] d. Using an inert gas as a carrier gas, the oxidation precursor is added into the reaction chamber in a pulsed manner for oxidation treatment;

[0017] e. Repeat steps b to d, with the number of cycles ≥ 1.

[0018] Furthermore, in the step b, the deposition temperature is 200-300° C., the pulse time is 300-800 s, and the pressure in the reaction chamber is 200-400 mTorr.

[0019] Furthermore, in step b, the reaction precursor comprises one or more of Ta(OCH2CH3)5, TaCl5, Ta(N(CH3)2)5, Al(CH3)3, TiCl4, TiI, ZrCl4, ZrI4 and Zr(OC(CH3)3)4, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the reaction precursor in the reaction chamber is 5 to 20 s.

[0020] Furthermore, in step d, the oxidizing precursor comprises one or more of water vapor, oxygen and ozone.

[0021] Furthermore, in the step d, the pulse time is 400 to 850 seconds, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the oxidation precursor in the reaction chamber is 15 to 60 seconds.

[0022] Furthermore, the inert gas independently comprises nitrogen and / or argon, and the temperature of the oxidation treatment is 200-300°C.

[0023] Furthermore, the annealing temperature is 300-500° C., and the annealing time is 2-5 hours.

[0024] Furthermore, the content of the metal oxide layer in the silicon-carbon negative electrode material is 0.1-1 wt%.

[0025] The present invention provides a silicon-carbon negative electrode material, comprising silicon-carbon composite particles and a metal oxide layer coated on the surface of the silicon-carbon composite particles, wherein the silicon-carbon composite particles contain 10 to 90% C and 10 to 90% Si, and the metal oxide contained in the metal oxide layer is M x O y , wherein M is Ta, Al, Ti or Zr, 0<x≤2, 0<y≤5.

[0026] Beneficial effects of the present invention:

[0027] (1) The negative electrode material of the present invention uses an atomic layer deposition method during the preparation process to deposit metal oxides on the porous silicon-carbon composite skeleton to inhibit the occurrence of interface side reactions between the electrolyte and the substrate surface.

[0028] (2) The coated tantalum oxide of the present invention has good electrical conductivity, thermal stability, corrosion resistance, and excellent electrochemical properties. The capacity reaches 1800-2300 mAh / g, the initial efficiency is 90-95%, and the capacity retention rate after 100 cycles is 88.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic diagram of the structure of the silicon-carbon negative electrode material prepared in Example 1 of the present invention;

[0030] Figure 2 The figure is a flow chart for preparing the silicon-carbon negative electrode material of the present invention. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0032] (1) obtaining a metal oxide layer on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the metal oxide layer;

[0033] (2) annealing the silicon-carbon composite particles coated with the metal oxide layer to obtain a silicon-carbon negative electrode material;

[0034] The metal oxide contained in the metal oxide layer is M x O y , wherein M is Ta, Al, Ti or Zr, 0<x≤2, 0<y≤5.

[0035] In the present invention, the atomic layer deposition method comprises the following steps:

[0036] a. Loading silicon-carbon composite particles on a reaction chamber carrier, evacuating the reaction chamber, and passing an inert gas;

[0037] b. Using an inert gas as a carrier gas, a reaction precursor is added into the reaction chamber in a pulsed manner for deposition;

[0038] c. After the deposition is completed, the reaction chamber is evacuated by passing inert gas;

[0039] d. Using an inert gas as a carrier gas, the oxidation precursor is added into the reaction chamber in a pulsed manner for oxidation treatment;

[0040] e. Repeat steps b to d, with the number of cycles ≥ 1.

[0041] In the present invention, the silicon-carbon composite particles are prepared by the method disclosed in patent CN117457873A, and the average particle size of the silicon-carbon composite particles is 10 μm.

[0042] In the present invention, in the step b, the deposition temperature is 200-300°C, preferably 220-280°C, and more preferably 250°C; the pulse time is 300-800s, preferably 400-700s, and more preferably 500-600s; the pressure in the reaction chamber is 200-400mTorr, and preferably 300mTorr.

[0043] In the present invention, in step b, the reaction precursor comprises one or more of Ta(OCH2CH3)5, TaCl5, Ta(N(CH3)2)5, Al(CH3)3, TiCl4, TiI, ZrCl4, ZrI4 and Zr(OC(CH3)3)4, preferably one or more of Ta(OCH2CH3)5, TaCl5 and Ta(N(CH3)2)5.

[0044] In the present invention, in step b, the flow rate of the carrier gas is 15-25 sccm, preferably 18-22 sccm, and more preferably 20 sccm; the residence time of the reaction precursor in the reaction chamber is 5-20 s, preferably 8-18 s, and more preferably 10-15 s.

[0045] In the present invention, in step d, the oxidizing precursor comprises one or more of water vapor, oxygen and ozone, preferably oxygen.

[0046] In the present invention, in the step d, the pulse time is 400 to 850 s, preferably 500 to 800 s, and more preferably 600 to 700 s; the flow rate of the carrier gas is 15 to 25 sccm, preferably 18 to 22 sccm, and more preferably 20 sccm; the residence time of the oxidative precursor in the reaction chamber is 15 to 60 s, preferably 20 to 50 s, and more preferably 30 to 40 s.

[0047] In the present invention, the inert gas independently comprises nitrogen and / or argon, preferably nitrogen.

[0048] In the present invention, in the step d, the temperature of the oxidation treatment is 200-300°C, preferably 220-280°C, and more preferably 250°C.

[0049] In the present invention, the annealing temperature is 300-500°C, preferably 350°C, 400°C, 450°C, 500°C; the annealing time is 2-5h, preferably 3-4h, and more preferably 3.5h.

[0050] In the present invention, the content of the metal oxide layer in the silicon-carbon negative electrode material is 0.1-1 wt %, preferably 0.2-0.9 wt %, and more preferably 0.3-0.8 wt %.

[0051] The present invention provides a silicon-carbon negative electrode material, comprising silicon-carbon composite particles and a metal oxide layer coated on the surface of the silicon-carbon composite particles, wherein the silicon-carbon composite particles contain 10 to 90% C and 10 to 90% Si, and the metal oxide contained in the metal oxide layer is M x O y , wherein M is Ta, Al, Ti or Zr, 0<x≤2, 0<y≤5.

[0052] In the present invention, the C content in the silicon-carbon composite particles is 10-90%, preferably 20-80%, and more preferably 30-70%; the Si content is 10-90%, preferably 20-80%, and more preferably 30-70%.

[0053] In the present invention, the metal oxide contained in the metal oxide layer is preferably Ta2O5, Al2O3, TiO2 or ZrO2.

[0054] The present invention establishes a new silicon-carbon negative electrode material based on the original CN 117457873 A patent. The atomic layer deposition tantalum oxide prepared by this method not only has the structural stability of porous materials, but also has good conductivity and corrosion resistance. The material inhibits the dissolution of silicon and carbon elements at the interface, inhibits the increase in the thickness of organic matter in the SEI film at the interface during the material recycling process, is more conducive to the transmission of lithium ions, and thus improves the rate performance of the Si / C composite material.

[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0056] Example 1

[0057] The silicon-carbon negative electrode material of the present invention comprises silicon-carbon composite particles and a tantalum oxide layer coated on the surface of the silicon-carbon composite particles; the silicon-carbon composite particles are prepared by the method of Example 4 in CN117457873A, with an average particle size of 10 μm and a thickness of the tantalum oxide layer of about 0.8 nm.

[0058] The method for preparing the silicon-carbon negative electrode material of this embodiment comprises the following steps:

[0059] (1) obtaining silicon-carbon composite particles; obtaining a tantalum oxide layer on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the tantalum oxide layer, specifically:

[0060] a. Load the silicon-carbon composite particles on the reaction chamber carrier of the atomic layer deposition equipment, evacuate the reaction chamber, and pass inert gas; set the deposition temperature to 220° C. and the pressure in the reaction chamber to 200 mTorr;

[0061] b. Using nitrogen as the carrier, the reaction precursor bottle source is Ta(N(CH3)2)5, which is added into the reaction chamber in a pulsed manner, with a pulse time of 450s and a carrier gas flow rate of 25sccm. The residence time of the reaction precursor in the reaction chamber is 15s;

[0062] c. Clean the reaction chamber with nitrogen gas and evacuate it;

[0063] d. Adding a nitrogen-loaded oxidation precursor into the reaction chamber in a pulsed manner, setting the pulse time to 650 s, the carrier gas flow rate to 15 sccm, the residence time of the oxidation precursor in the reaction chamber to 20 s, and the oxidation precursor being water vapor;

[0064] e. Repeat steps b to d until the tantalum source is deposited once, which is one deposition cycle. The number of deposition cycles is 5. The obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@1Ta2O5.

[0065] (2) The silicon-carbon composite particles coated with the tantalum oxide layer are annealed at a temperature of 400° C. for 2 h to obtain the novel silicon-carbon negative electrode material.

[0066] Example 2

[0067] The difference between the silicon-carbon negative electrode material described in this embodiment and that in Embodiment 1 is that the thickness of tantalum oxide is different. The deposition thickness of this embodiment is about 2.5 nm.

[0068] The difference between the silicon-carbon composite negative electrode material described in this embodiment and that in Embodiment 1 lies in the number of deposition cycles. The number of deposition cycles in the embodiment is 10, and the obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@2Ta2O5.

[0069] Example 3

[0070] The difference between the silicon-carbon negative electrode material described in this embodiment and that in Embodiment 1 is that the thickness of tantalum oxide is different. The deposition thickness of this embodiment is about 3.9 nm.

[0071] The difference between the silicon-carbon composite negative electrode material described in this embodiment and that in Embodiment 1 lies in the number of deposition cycles. The number of deposition cycles in the embodiment is 15 times, and the obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@3Ta2O5.

[0072] Example 4

[0073] The difference between the silicon-carbon negative electrode material described in this embodiment and that in Embodiment 1 is that the thickness of tantalum oxide is different. The deposition thickness of this embodiment is about 5 nm.

[0074] The difference between the silicon-carbon composite negative electrode material described in this embodiment and that in Embodiment 1 lies in the number of deposition cycles. The number of deposition cycles in the embodiment is 20 times, and the obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@4Ta2O5.

[0075] Example 5

[0076] The difference between the silicon-carbon negative electrode material described in this embodiment and that in Embodiment 1 is that the thickness of tantalum oxide is different. The deposition thickness of this embodiment is about 6.2 nm.

[0077] The difference between the silicon-carbon composite negative electrode material described in this embodiment and that in Embodiment 1 lies in the number of deposition cycles. The number of deposition cycles in the embodiment is 25 times, and the obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@5Ta2O5.

[0078] Example 6

[0079] The difference between the silicon-carbon negative electrode material described in this embodiment and that in embodiment 1 is that the thickness of tantalum oxide is different. The deposited thickness of the metal oxide layer in this embodiment is about 4 nm.

[0080] The method for preparing the silicon-carbon negative electrode material of this embodiment comprises the following steps:

[0081] (1) obtaining silicon-carbon composite particles; obtaining a tantalum oxide layer on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the tantalum oxide layer, specifically:

[0082] a. Load the silicon-carbon composite particles on the reaction chamber carrier of the atomic layer deposition equipment, evacuate the reaction chamber, and pass inert gas; set the deposition temperature to 220° C. and the pressure in the reaction chamber to 250 mTorr;

[0083] b. Using inert gas nitrogen as a carrier, the reaction precursor tantalum ethoxide is added into the reaction chamber in a pulsed manner. The reaction precursor is a tantalum source. The pulse time is 400 seconds, the carrier gas flow rate is 15 sccm, and the residence time of the reaction precursor in the reaction chamber is 12 seconds.

[0084] c. Clean the reaction chamber with nitrogen and evacuate it;

[0085] d. Using nitrogen gas as a carrier, ozone, an oxidative precursor, was added into the reaction chamber in a pulsed manner. The pulse time was set to 400 s, the carrier gas flow rate was 22 sccm, and the residence time of the oxidative precursor in the reaction chamber was 15 s.

[0086] e. Repeat steps b to d until the tantalum source is deposited once, which is one deposition cycle. The number of deposition cycles is 17. The obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@6Ta2O5.

[0087] (2) The silicon-carbon composite particles coated with the aluminum oxide layer are annealed at a temperature of 350° C. for 4 hours to obtain the novel silicon-carbon composite negative electrode material.

[0088] Example 7

[0089] The difference between the silicon-carbon negative electrode material described in this embodiment and that in Embodiment 1 is that the thickness of tantalum oxide is different. The deposited thickness of the metal oxide layer in this embodiment is about 4.1 nm.

[0090] (1) obtaining silicon-carbon composite particles; obtaining a tantalum oxide layer on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the tantalum oxide layer, specifically:

[0091] a. Load the silicon-carbon composite particles on the reaction chamber carrier of the atomic layer deposition equipment, evacuate the reaction chamber, and pass inert gas; set the deposition temperature to 280° C. and the pressure in the reaction chamber to 350 mTorr;

[0092] b. Use inert gas as a carrier reaction precursor TaCl5, add it into the reaction chamber in a pulsed manner, the reaction precursor is a tantalum source, the time is 400s, the carrier gas flow rate is 15sccm, and the residence time of the reaction precursor in the reaction chamber is 30s;

[0093] c. Clean the reaction chamber with nitrogen and evacuate it;

[0094] d. Using nitrogen gas as a carrier, the water vapor of the oxidation precursor is added into the reaction chamber in a pulsed manner. The pulse time is set to 400 ms, the carrier gas flow rate is 22 sccm, and the residence time of the oxidation precursor in the reaction chamber is 25 s.

[0095] e. Repeat steps b to d until the tantalum source is deposited once, which is one deposition cycle. The number of deposition cycles is 17. The obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@7Ta2O5.

[0096] (2) The silicon-carbon composite particles coated with the tantalum oxide layer are annealed at a temperature of 450° C. for 3 hours to obtain the novel silicon-carbon composite negative electrode material.

[0097] Example 8

[0098] The difference between the silicon-carbon negative electrode material described in this embodiment and that in embodiment 1 is that the reaction precursor is different, and an inert gas is used to load the reaction precursor Al(CH3)3. The deposition thickness of this embodiment is about 2.1 nm.

[0099] (1) obtaining silicon-carbon composite particles; obtaining an aluminum oxide layer on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the aluminum oxide layer, specifically:

[0100] a. Load the silicon-carbon composite particles on the reaction chamber carrier of the atomic layer deposition equipment, evacuate the reaction chamber, and pass inert gas; set the deposition temperature to 220° C. and the pressure in the reaction chamber to 200 mTorr;

[0101] b. Using nitrogen as the carrier, the reaction precursor bottle source is Al(CH3)3, which is added into the reaction chamber in a pulsed manner, with a pulse time of 450s, a carrier gas flow rate of 25sccm, and the residence time of the reaction precursor in the reaction chamber is 15s;

[0102] c. Clean the reaction chamber with nitrogen gas and evacuate it;

[0103] d. Adding a nitrogen-loaded oxidation precursor into the reaction chamber in a pulsed manner, setting the pulse time to 650 s, the carrier gas flow rate to 15 sccm, the residence time of the oxidation precursor in the reaction chamber to 20 s, and the oxidation precursor being water vapor;

[0104] e. Repeat steps b to d until the tantalum source is deposited once, which is one deposition cycle. The number of deposition cycles is 10. The obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@Al2O3.

[0105] (2) The silicon-carbon composite particles coated with the aluminum oxide layer are annealed at a temperature of 400° C. for 2 h to obtain the novel silicon-carbon negative electrode material.

[0106] Example 9

[0107] The difference between the silicon-carbon negative electrode material described in this embodiment and that in embodiment 1 is that the reaction precursor is different, and an inert gas is used to load the reaction precursor TiI. The deposition thickness of this embodiment is about 2.5 nm (1) to obtain silicon-carbon composite particles; an atomic layer deposition method is used to obtain a titanium oxide layer on the surface of the silicon-carbon composite particles to obtain silicon-carbon composite particles coated with a titanium oxide layer, specifically:

[0108] a. Load the silicon-carbon composite particles on the reaction chamber carrier of the atomic layer deposition equipment, evacuate the reaction chamber, and pass inert gas; set the deposition temperature to 220° C. and the pressure in the reaction chamber to 200 mTorr;

[0109] b. Using nitrogen as the carrier, the reaction precursor bottle source is TiI, which is added into the reaction chamber in a pulsed manner, with a pulse time of 450s, a carrier gas flow rate of 25sccm, and the residence time of the reaction precursor in the reaction chamber is 15s;

[0110] c. Clean the reaction chamber with nitrogen gas and evacuate it;

[0111] d. Adding a nitrogen-loaded oxidation precursor into the reaction chamber in a pulsed manner, setting the pulse time to 650 s, the carrier gas flow rate to 15 sccm, the residence time of the oxidation precursor in the reaction chamber to 20 s, and the oxidation precursor being water vapor;

[0112] e. Repeat steps b to d until the tantalum source is deposited once, which is one deposition cycle. The number of deposition cycles is 10. The obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@TiO2.

[0113] (2) The silicon-carbon composite particles coated with the titanium oxide layer are annealed at a temperature of 400° C. for 2 h to obtain the novel silicon-carbon negative electrode material.

[0114] Example 10

[0115] The difference between the silicon-carbon negative electrode material described in this embodiment and that in embodiment 1 is that the reaction precursor is different, and an inert gas is used as the loading reaction precursor Zr(OC(CH3)3)4. The deposition thickness of this embodiment is about 2.5nm (1) to obtain silicon-carbon composite particles; an atomic layer deposition method is used to obtain a zirconium oxide layer on the surface of the silicon-carbon composite particles to obtain silicon-carbon composite particles coated with a zirconium oxide layer, specifically:

[0116] a. Load the silicon-carbon composite particles on the reaction chamber carrier of the atomic layer deposition equipment, evacuate the reaction chamber, and pass inert gas; set the deposition temperature to 220° C. and the pressure in the reaction chamber to 200 mTorr;

[0117] b. Using nitrogen as the carrier, the reaction precursor bottle source is Zr(OC(CH3)3)4, which is added into the reaction chamber in a pulsed manner, with a pulse time of 450s and a carrier gas flow rate of 25sccm. The residence time of the reaction precursor in the reaction chamber is 15s;

[0118] c. Clean the reaction chamber with nitrogen gas and evacuate it;

[0119] d. Adding a nitrogen-loaded oxidation precursor into the reaction chamber in a pulsed manner, setting the pulse time to 650 s, the carrier gas flow rate to 15 sccm, the residence time of the oxidation precursor in the reaction chamber to 20 s, and the oxidation precursor being water vapor;

[0120] e. Repeat steps b to d until the tantalum source is deposited once, which is one deposition cycle. The number of deposition cycles is 10. The obtained composite silicon-carbon negative electrode material is recorded as (C / Si)@ZrO2.

[0121] (2) The silicon-carbon composite particles coated with the zirconium oxide layer are annealed at a temperature of 400° C. for 2 hours to obtain the novel silicon-carbon negative electrode material.

[0122] Comparative Example 1

[0123] The straw-based porous carbon material was placed in a rotary kiln, and monosilane was introduced under nitrogen protection, with a monosilane gas flow rate: nitrogen flow rate = 1:9, and a deposition temperature of 400°C; after the silane deposition was completed, methane was introduced under nitrogen protection, with a methane flow rate: nitrogen flow rate = 1:9; Si: carbon skeleton = 1:1. After the deposition was completed, the furnace was cooled to obtain a silicon-carbon negative electrode material.

[0124] Comparative Example 2

[0125] The porous carbon material of sucrose is added into a rotary kiln, and monosilane is introduced under nitrogen protection, with the monosilane gas flow rate: nitrogen flow rate = 1:9, and the deposition temperature is 400°C; after the silane deposition is completed, methane is introduced under nitrogen protection, with the methane flow rate: nitrogen flow rate = 1:9; Si: carbon skeleton = 1:1. After the deposition is completed, the furnace is cooled to obtain a silicon-carbon negative electrode material.

[0126] The performance of the silicon-carbon negative electrode materials obtained in the examples and comparative examples was tested, and the results are shown in Table 1 below.

[0127] Table 1 Test results

[0128]

[0129] It can be seen from the above embodiments that the present invention provides a silicon-carbon negative electrode material and a preparation method thereof. The composite material of the present invention is prepared by using an atomic layer deposition method to deposit tantalum oxide on a porous silicon-carbon composite skeleton to inhibit the occurrence of interface side reactions between the electrolyte and the substrate surface. Among them, the coating thickness of Example 3 is about 3.9nm, and the performance shown is the best. The first charge specific capacity is 2282mAh / g, and the first efficiency reaches 94.6%. As the number of deposition cycles increases, the thickness increases, which is not conducive to the diffusion of lithium ions, resulting in a decrease in capacity and first efficiency, and the capacity retention rate is also slightly reduced. The coated structure tantalum oxide of the present invention has good conductivity, thermal stability, and corrosion resistance, and has excellent electrochemical properties. The capacity reaches 1800-2300mAh / g, the first efficiency is 90-95%, and the capacity retention rate can reach 92.3% after 50 cycles.

[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: (1) obtaining a metal oxide layer on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the metal oxide layer; (2) annealing the silicon-carbon composite particles coated with the metal oxide layer to obtain a silicon-carbon negative electrode material; The metal oxide contained in the metal oxide layer is M x O y , wherein M is Ta, Al, Ti or Zr, 0<x≤2, 0<y≤5.

2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The atomic layer deposition method comprises the following steps: a. Loading silicon-carbon composite particles on a reaction chamber carrier, evacuating the reaction chamber, and passing an inert gas; b. Using an inert gas as a carrier gas, a reaction precursor is added into the reaction chamber in a pulsed manner for deposition; c. After the deposition is completed, the reaction chamber is evacuated by passing inert gas; d. Using an inert gas as a carrier gas, the oxidation precursor is added into the reaction chamber in a pulsed manner for oxidation treatment; e. Repeat steps b to d, with the number of cycles ≥ 1.

3. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: In the step b, the deposition temperature is 200-300° C., the pulse time is 300-800 s, and the pressure in the reaction chamber is 200-400 mTorr.

4. The method for preparing the silicon-carbon negative electrode material according to claim 2 or 3, characterized in that: In the step b, the reaction precursor includes one or more of Ta(OCH2CH3)5, TaCl5, Ta(N(CH3)2)5, Al(CH3)3, TiCl4, TiI, ZrCl4, ZrI4 and Zr(OC(CH3)3)4, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the reaction precursor in the reaction chamber is 5 to 20 s.

5. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In the step d, the oxidizing precursor comprises one or more of water vapor, oxygen and ozone.

6. The method for preparing the silicon-carbon negative electrode material according to claim 2, 3 or 5, characterized in that: In the step d, the pulse time is 400 to 850 seconds, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the oxidation precursor in the reaction chamber is 15 to 60 seconds.

7. The method for preparing the silicon-carbon negative electrode material according to claim 2 or 5, characterized in that: The inert gas independently includes nitrogen and / or argon, and the temperature of the oxidation treatment is 200-300°C.

8. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The annealing temperature is 300-500° C., and the annealing time is 2-5 hours.

9. The method for preparing the silicon-carbon negative electrode material according to claim 1 or 8, characterized in that: The content of the metal oxide layer in the silicon-carbon negative electrode material is 0.1-1 wt%.

10. The silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The invention comprises silicon-carbon composite particles and a metal oxide layer coated on the surface of the silicon-carbon composite particles, wherein the content of C in the silicon-carbon composite particles is 10-90%, the content of Si is 10-90%, and the metal oxide contained in the metal oxide layer is M x O y , wherein M is Ta, Al, Ti or Zr, 0<x≤2, 0<y≤5.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN115966684A

  • Silicon-carbon composite negative electrode material and preparation method thereof

    CN117457873A

Cited By

  • Desolvation layer modified silicon-carbon negative electrode and preparation method thereof

    CN120413631A

  • Silicon-based negative electrode material and preparation method and application thereof

    CN120432516A

  • Carbon-coated multi-element synergistic silicon-carbon negative electrode material as well as preparation method and application thereof

    CN120690843A